2006
DOI: 10.1097/01.aog.0000195356.90589.c5
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Views of Prenatal Violence Screening

Abstract: II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Differences also emerged in regard to socio-economic characteristics, with younger women feeling more embarrassed by routine or case-based inquiry than older women [19,20] and women with a high school degree or higher income being more likely to oppose it [20,23]. As it has been reported before, health care providers are often hesitant to inquire about intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…Differences also emerged in regard to socio-economic characteristics, with younger women feeling more embarrassed by routine or case-based inquiry than older women [19,20] and women with a high school degree or higher income being more likely to oppose it [20,23]. As it has been reported before, health care providers are often hesitant to inquire about intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…Strong evidence exists that women experiencing abuse do not self-disclose their situations during routine prenatal care, but respond to provider-initiated inquiry [18,19]. Furthermore, despite the increased number of contacts with healthcare providers in the course of routine prenatal care and higher utilization of medical services, few providers routinely assess pregnant and postpartum women for abuse [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of high levels of acceptability and disclosure reported using computer screening [46,47], we established that e-screening would be feasible if, in the intervention group, 85% of women indicated that they were able to tell the truth on all questions on the psychosocial assessment (question 7 of the computer assessment evaluation, CAE). For our other outcomes, we based the sample size calculation on 85% of women scoring 4-8 on the Risk subscale of the Disclosure Expectations Scale and 85% scoring 16-20 on the Utility subscale of the Disclosure Expectations Scale.…”
Section: Methodsmentioning
confidence: 99%
“…We measured women’s views on the feasibility and acceptability of e-screening with an adapted 9-item version of Renker and Tonkin’s assessment of the feasibility of computerized screening for interpersonal violence [46,47]. Of the 9 items, 2 items are related to acceptability of e-screening (I did or would like to use a tablet to answer these questions about emotional health; I would prefer answering questions about emotional health on the tablet compared to a paper questionnaire) and the remaining 7 items measure broad areas of feasibility, including disclosure (I was able to tell the truth on all the questions about emotional health; I did not like answering the questions about emotional health on the tablet or paper because it was hard to answer how I really felt), features of screening (privacy; ease of understanding questions; impersonal; time to completion), and comparison with paper-based screening.…”
Section: Methodsmentioning
confidence: 99%